Verifying BON models with alloy - Demasi, Ramiro Adrián (2005)
In this paper we describe a methodology to translate BON (architectural) designs to Alloy specifications. The main virtue of this process is that it can be implemented by means of software tools. The utilization of this methodology during the software development allows designers to validate different kinds of properties over their BON models. Allowing, in this way, the finding of critical bugs in earlier steps of system construction. Finally, we present a software which implements this translation from BON to Alloy.